A palaeoparasitological analysis of rodent coprolites from the Cueva Huenul 1 archaeological site in Patagonia (Argentina) - Beltrame, M.O. (2012)
The aim of the present study was to examine the parasite fauna present in rodent coprolites collected from Cueva Huenul 1 (CH1), northern Neuquén (Patagonia, Argentina), an archaeological site that provides stratified sequences of archaeological and palaeontological remains dating from the Late Pleistocene/Early Holocene Transition to the Late Holocene period. Twenty rodent coprolites collected from different sedimentary units from the site, with ages ranging from 13.844 ± 75-1.416 ± 37 years BP, were examined for parasites. Each coprolite was processed as a whole: rehydrated, homogenised, spontaneously sedimented and examined using light microscopy. The coprolites and the eggs of any parasites present were described, measured and photographed. In all, 158 parasite eggs were found in 10 coprolites. The faeces were positive for Viscachataenia quadrata Denegri, Dopchiz, Elissondo & Beveridge and Monoecocestus sp. Beddard (Cestoda: Anoplocephalidae) and for Heteroxynema (Cavioxyura) viscaciae Sutton & Hugot (Nematoda: Oxyuridae). The coprolites examined were tentatively attributed to Lagidium viscacia Molina (Mammalia, Rodentia, Caviomorpha, Chinchillidae). The life cycles of these parasites are discussed.